Study guides

Q: Which expression is equivalent to 8c plus 6-3c-2?

Write your answer...

Submit

Related questions

6

It is an expression that can be simplified to: 1-4b-5c

The expression simplified is: 7d-2cd-5c

Seven, though they can be reduced to 3 if like terms are combined.

It is: 6-11+5-8c+9c = c

It is 7 - 8c.

What is the answer

8c

It is 7 - 8c.

No

8c + 24 + 23 = 71subtract 47 from each side, 8c = 24divide each side by 8, c = 3

-8c+1 = -3 -8c = -3-1 -8c = -4 Divide both sides by -8 in order to find the value of c remembering that a minus number divided into minus number is equal to a plus number: c = 1/2

4c(-sq+2)

-8c + 1 = -3 => -8c = -3 + 1 => -8c = -2 => c = -2/(-8) => c = 1/4 = 0.25

It is an equation and the value of c is -7

The GCF is 8c.

If you mean: 2c+2+6c-4 then it is 8c-2 when simplified.

20+40c is the answer.

the final episode is monday November 23rd at 9/8c

4-8c in pharenhite = -4

8c=10pt

2. c2 + c2 + 8 = 8c 2c2 - 8c + 8 = 0 c2 - 4c + 4 = 0 (c - 2)(c - 2) = 0 (c - 2)2 = 0 c - 2 = 0 c = 2

It is not possible to solve a linear equation in two unknowns without knowing one of them.

4(8c - 7)(8c + 7)

If 8c = 60, then c = 60/8 = 7.5.